Performance Evaluation of Demodulation Methods: a Combinatorial Approach - Daniel Krob; Ekaterina A. Vassilieva (Discrete Mathematics & Theoretical Computer Science, 2001)
This paper provides a combinatorial approach for analyzing the performance of demodulation methods used in GSM. We also show how to obtain combinatorially a nice specialization of an important performance evaluation formula, using its connection with a classical bijection of Knuth between pairs of Young tableaux and {0,1}-matrices.